The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12872-022-02688-5
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in cardiac function in Duchenne muscular dystrophy population as measured by magnetic resonance imaging

Abstract: Background The lack of dystrophin in cardiomyocytes in Duchenne muscular dystrophy (DMD) is associated with progressive decline in cardiac function eventually leading to death by 20–40 years of age. The aim of this prospective study was to determine rate of progressive decline in left ventricular (LV) function in Duchenne muscular dystrophy (DMD) over 5 years. Methods Short axis cine and grid tagged images of the LV were acquired in individuals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“… 17 , 23 , 24 Several studies have examined the role of myocardial strain in patients with MD. 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 23 , 24 Several studies have examined the role of myocardial strain in patients with MD. 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Recognizing LVEF is a well‐established prognostic marker in patients with MD, our study provided objective evidence that myocardial strain delivers incremental prognostic value to LVEF in this vulnerable patient population. 27 , 28 Although speckle‐tracking echocardiography can be used for strain‐based evaluations, its performance can be hindered because of limited acoustic windows as a result of scoliosis, obesity, and lung disease, 9 , 30 which are highly prevalent in patients with MD. 5 CMR imaging is the preferred method for myocardial strain analysis as a high‐resolution, accurate, and reproducible alternative to echocardiography, 11 , 31 , 32 which supports the impact of CMR imaging as part of routine clinical care in patients with MD.…”
Section: Discussionmentioning
confidence: 99%
“…CMR strain correlates more closely with CMR LVEF compared to TTE strain (Buddhe et al, 2016). A sensitive marker used to identify cardiac pathology is peak circumferential strain (εcc) at the mid-ventricular level, which can also assess effects of therapeutic interventions on cardiac function and measure the degree of cardiac pathology (Hor et Batra et al, 2022). This measure was able to detect cardiac pathology as early as 5 years of age and the findings of this study revealed the heterogeneity in cardiac progression in patients with DMD (Batra et al, 2022).…”
Section: Cardiac Magnetic Resonance Imagingmentioning
confidence: 74%
“…The LVEF decline is similar to that of prior single and multicenter studies, suggesting that the cohort is generalizable. [16][17][18] Most trials will be 1 or 2 years in duration and a comprehensive understanding of the change in biomarkers over time is necessary to adequately power a trial. Therefore, our data focuses on 1-and 2-year progression in DMD.…”
Section: Discussionmentioning
confidence: 99%